Exploiting Plant Volatile Organic Compounds (VOCs) in Agriculture to Improve Sustainable Defense Strategies and Productivity of Crops - Brilli, Federico; Loreto, Francesco; Baccelli, Ivan (Frontiers in Plant Science, 2019)
There is an urgent need for new sustainable solutions to support agriculture in facing current environmental challenges. In particular, intensification of productivity and food security needs require sustainable exploitation of natural resources and metabolites. Here, we bring the attention to the agronomic potential of volatile organic compounds (VOCs) emitted from leaves, as a natural and eco-friendly solution to defend plants from stresses and to enhance crop production. To date, application of VOCs is often limited to fight herbivores. Here we argue that potential applications of VOCs are much wider, as they can also protect from pathogens and environmental stresses. VOCs prime plant’s defense mechanisms for an enhanced resistance/tolerance to the upcoming stress, quench reactive oxygen species (ROS), have potent antimicrobial as well as allopathic effects, and might be important in regulating plant growth, development, and senescence through interactions with plant hormones. Current limits and drawbacks that may hamper the use of VOCs in open field are analyzed, and solutions for a better exploitation of VOCs in future sustainable agriculture are envisioned.